EXPERIENCE OF ADMINISTRATION OF MILK FORMULA «NESTOGEN 1» IN HEALTHY CHILDREN OF FIRST SIX MONTHS OF LIFE - O.V. Zaitseva; V.A. Pastukhova; E.V. Moiseeva; S.V. Zaitseva; N.A. Aleksandrina; T.N. Praznikova; T.L. Borisova; E.E. Lokshina ("Paediatrician" Publishers LLC, 2008)
The activity of adapted milk formula «Nestogen 1» was investigated on healthy children of first six months of life, including patients with functional disorders of gastrointestinal tract. «Nestogen 1» was used as supplementary feeding or prime feeding in absence of breast milk. The increase of body weight and growth in children with these types of feeding was similar to age specific norm. Comfortable digestion provides abatement of intestinal colic, normalization of stool frequency and characteristics. Co program index improved and optimal intestinal micribiocenose restored in four weeks. There was no any allergic reaction or side effects during investigation.Key words: healthy children, rearing, adapted milk formula «Nestogen 1».